Western Psychology and Muslim Psychology in Dialogue: Comparisons Between a Qura'nic Theory of Personality and Freud's and Jung's Ideas - Abu-Raiya, Hisham (Journal of religion and health, 2014)
In this paper, comparisons are made between a newly developed Qura'nic theory of personality and the Freudian and Jungian theories of the mind. Notable similarities were found between the Freudian id, ego, superego and neurosis and the Qura'nic nafs ammarah besoa' (evil-commanding psyche), a'ql (intellect), al-nafs al-lawammah (the reproachful psyche) and al-nafs al-marid'a (the sick psyche), respectively. Noteworthy resemblances were detected also between the Jungian concepts collective unconscious, archetypes, Self and individuation and the Qura'nic constructs roh (spirit), al-asmaa' (the names), qalb (heart), and al-nafs al-mutmainnah (the serene psyche), respectively. These parallels, as well as the departure points, between the models are thoroughly discussed and analyzed. The comparisons performed in this paper open new avenues for dialogue between western models of the psyche and their Muslim counterparts, a dialogue that can enrich both perspectives and advance the field of psychology.